Association of haematological parameters with thyroid dysfunction in non-pregnant women of reproductive age of Western Bihar - Kumar, Binay; Prasad, Nidhi (International Journal of Research in Medical Sciences, 2025)
Background: The interplay between thyroid imbalances and anaemia holds significant importance, particularly in non-pregnant women of childbearing age. Thyroid hormones are pivotal for erythropoiesis. Disruptions in thyroid function often exacerbate nutrient deficiencies, further aggravating anaemia. In western Bihar, where the prevalence of thyroid dysfunction and anaemia is notable, exploring this relationship is crucial for advancing women's health. Regular screening for thyroid dysfunction in anaemic patients, and vice versa, can significantly enhance diagnosis, management, and overall health outcomes. This study aims to assess haematological parameters in non-pregnant women of reproductive age across three thyroid hormonal statuses: euthyroid, hypothyroid, and hyperthyroid. Methods: This record-based study spanned from January to December 2024, involving 225 non-pregnant females aged 18-45 years who visited clinical OPDs. Participants were divided into three groups (75 each): hypothyroidism, hyperthyroidism, and euthyroid controls. Haematological parameters were analyzed using a 6-part autoanalyzer for CBC, Leishman-stained PBS for RBC morphology, and thyroid function tests (TFT) conducted on a Vitros analyzer. A p<0.05 was considered statistically significant. Results: Significant differences were observed in haemoglobin, RBC count, and total count between hypothyroid and hyperthyroid groups. RDW and AEC were elevated in hypothyroid cases, though within normal limits. MCV showed no significant variation, indicating normocytic anaemia in the hypothyroid group. Conclusions: These findings highlight the profound impact of thyroid dysfunction on haematological health. Evaluating thyroid status in unexplained anaemia is essential, particularly in rural areas like western Bihar, to restore health and improve women's quality of life.